Impact of time-of-day on diffusivity measures of brain tissue derived from diffusion tensor imaging - Thomas, Cibu; Sadeghi, Neda; Nayak, Amrita; Trefler, Aaron; Sarlls, Joelle; Baker, Chris I.; Pierpaoli, Carlo (NeuroImage (Orlando, Fla.), 2018)
Diurnal fluctuations in MRI measures of structural and functional properties of the brain have been reported recently. These fluctuations may have a physiological origin, since they have been detected using different MRI modalities, and cannot be explained by factors that are typically known to confound MRI measures. While preliminary evidence suggests that measures of structural properties of the brain based on diffusion tensor imaging (DTI) fluctuate as a function of time-of-day (TOD), the underlying mechanism has not been investigated. Here, we used a longitudinal within-subjects design to investigate the impact of time-of-day on DTI measures. In addition to using the conventional monoexponential tensor model to assess TOD-related fluctuations, we used a dual compartment tensor model that allowed us to directly assess if any change in DTI measures is due to an increase in CSF/free-water volume fraction or due to an increase in water diffusivity within the parenchyma. Our results show that Trace or mean diffusivity, as measured using the conventional monoexponential tensor model tends to increase systematically from morning to afternoon scans at the interface of grey matter/CSF, most prominently in the major fissures and the sulci of the brain. Interestingly, in a recent study of the glymphatic system, these same regions were found to show late enhancement after intrathecal injection of a CSF contrast agent. The increase in Trace also impacts DTI measures of diffusivity such as radial and axial diffusivity, but does not affect fractional anisotropy. The dual compartment analysis revealed that the increase in diffusivity measures from PM to AM was driven by an increase in the volume fraction of CSF-like free-water. Taken together, our findings provide important insight into the likely physiological origins of diurnal fluctuations in MRI measurements of structural properties of the brain. •Although diurnal fluctuations in MRI measures of structural and functional properties of the brain have been reported recently, the underlying physiological mechanisms are unclear.•Here, we first used diffusion tensor MRI to measures diurnal changes in diffusivity measures and found that Trace or mean diffusivity as measured using the conventional monoexponential tensor model, tends to increase systematically from morning to afternoon scans.•We then used a dual compartment tensor model that allowed us to directly assess if any change in DTI measures is due to an increase in CSF/free-water volume fraction and demonstrate that the increase in Trace from morning to afternoon can be explained by an increase in CSF-like free-water.•The time-of-day related changes are localized along the interface of grey matter and CSF and is most prominent along the major fissures and sulci of the brain, that have been associated with the glymphatic system.